Design of Shoes Production Tool - Yuliarty, Popy; Ramadhan, Rizky; Naro, Aulia; Afrizal, Reza (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2025)
This research was conducted on MSMEs that produce shoes and the like. Some production processes are carried out manually, which has an impact on employee occupational health. The uppersole installation process takes a long time with manual work which is certainly less effective because the position of the shoe changes and produces many unnecessary movements to position the shoe, impacting the condition of workers who experience several complaints such as pain in the thighs, back, and hands. This study aims to design a work aid for installing shoe uppersoles so that they can work effectively and avoid fatigue due to work positions. The design was carried out using the NIDA method. The results of the fixture design show that the fixture is able to withstand 12 directions of object movement, so that the processed upper sole can be maintained in a stationary state and no longer requires repeated positioning efforts. The results of this design can simplify the work process from previously 19 processes with a total time of 62 minutes to 15 processes with a total time of 54 minutes.